Enhancement of NTSA Secure Communication with One-Time Pad (OTP) in IoT - Alattas, Ali Hasan Aidaros; Al-Shareeda, Mahmood A.; Manickam, Selvakumar; Saare, Murtaja Ali (Informatica, 2023)
Internet of Things (IoT) systems use interconnected devices with limited processing, memory, storage, and power availability. Designing the IoT system requires careful consideration of data security. IoT networks are used to collect, process, and transport data; as a result, it needs to be encrypted and secured. To ensure that the data of IoT systems are protected, a variety of lightweight encryption techniques have been developed. These algorithms are unable to carry out complicated or extensive computations. The current challenge facing lightweight cryptographic algorithms, such as NTSA, is how to combine the highest level of security with the least amount of negative influence on runtime speed and space. By applying the One-Time Pad (OTP) technique, the proposed mechanism can raise the security level and effectiveness of NTSA. The proposed mechanism must be put into practise and put to the test in order to demonstrate its effectiveness and capacity to satisfy the needs of the resource-constrained devices. Due to the benefits of the OTP, this suggested method would be beneficial for devices with minimal resources. The proposed technique offers a greater security level, 2134, than NTSA, 2128, after examining and evaluating the experimental data noticed throughout the tests. NTSA is slower than the suggested approach by 70% in terms of runtime speed. While NTSA uses 16% of SRAM, the proposed algorithm only uses 12%. NTSA uses 70% more energy than the suggested algorithm, with higher energy consumption results of 0.000388 Joules for the proposed algorithm and 0.001295 Joules for NTSA.